PENGARUH E- PAYMENT TERHADAP PERILAKU KONSUMTIF MASYARAKAT (STUDI KASUS DI TIMBANG LANGKAT KECAMATAN BINJAI TIMUR KOTA BINJAI) - Muhammad Nafan Haikal; Elida Elfi Barus (Jurnal Ilmiah Ekonomi Dan Bisnis, 2025)
In the industrial era 5.0, technology is increasingly developing, including technology in Indonesia. The development of technology today affects people's lifestyles, one of which is that people become modern and easier, supported by the internet. The rapid development of the internet today has built an online trading system (E-Payment). E-Payment is an activity that includes distributing, selling, buying, marketing products via the internet. The ease of access to shopping on E-Payment is increasing with the support of payments using digital payments in shopping applications. This study aims to determine whether or not there is an influence of E-Payment and Digital Payment on Consumptive Behavior. In this study using quantitative research methods. The population in this study were people in Timbang Langkat kec.Binjai Timur Binjai City and obtained a sample of 200 people. The research method used is quantitative method with a measuring instrumentalikert scale with data analysis techniques using multiple linear regression using SPSS. Hypothesis testing using the t test and F test. while the results showed that partially E-Payment and digital payment had a significant effect on consumptive behavior by showing the tcount of 10.95 and 10.388 with a ttable value of 3.97 and a significant value of 0.00 <0.1 which means that E-Payment and digital payment simultaneously affect consumptive behavior.